2014
DOI: 10.1111/jcal.12049
|View full text |Cite
|
Sign up to set email alerts
|

Modeling preservice teachers’ TPACK competencies based on ICT usage

Abstract: The purpose of this study was to build a model that predicts the relationships between the Technological Pedagogical Content Knowledge (TPACK) competencies and information and communication technology (ICT) usages. Research data were collected from 3105 Turkish preservice teachers. The TPACK-Deep Scale, ICT usage phase survey and the ICT usage level survey were used to collect the research data. The structural regression model was conducted to test the model regarding the fact that ICT usage phases and ICT usa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
1
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(46 citation statements)
references
References 42 publications
(68 reference statements)
3
34
1
8
Order By: Relevance
“…Also, technology usage did not significantly affect teachers' technological pedagogical content knowledge (Saltan & Arslan, 2017), which contradicts an earier study showing that pre-service teachers using ICT have a higher technological pedagogical content knowledge (Kabakci Yurdakul & Coklar, 2014). Pedagogical content knowledge is important for a successful integration of technology in teaching (Marchis, 2013).…”
Section: Theoretical Backgroundcontrasting
confidence: 42%
“…Also, technology usage did not significantly affect teachers' technological pedagogical content knowledge (Saltan & Arslan, 2017), which contradicts an earier study showing that pre-service teachers using ICT have a higher technological pedagogical content knowledge (Kabakci Yurdakul & Coklar, 2014). Pedagogical content knowledge is important for a successful integration of technology in teaching (Marchis, 2013).…”
Section: Theoretical Backgroundcontrasting
confidence: 42%
“…Fransson ve Holmberg (2012) çalışmalarında öğrencilerin BİT araçları ile kendilerini daha özgür hissettiklerini belirtmiş ve TPİB'nin öğretmen eğitiminde öğrenme, öğretme ve değerlendirme boyutlarında kullanabileceğini ifade etmişlerdir. BİT kullanımını geliştiren kursların öğretmen adaylarının TPİB görüşleri üzerinde olumlu etkisinin olduğu ifade edilmektedir Chai, Koh, Tsai ve Tan 2011;Kabakçı Yurdakul ve Çoklar, 2014).…”
Section: Discussionunclassified
“…The importance of ICT competency levels in technopedagogical education competency acquisition was also emphasized in the studies conducted by Chai et al (2013) and by Koh et al (2013). Again, in their study, Kabakci Yurdakul, and Coklar (2014) concluded that ICT usage levels positively influenced TPACK competencies.…”
Section: Discussionmentioning
confidence: 85%